Distinct patterns of increased translocator protein in posterior cortical atrophy and amnestic Alzheimer's disease - Kreisl, William C.; Lyoo, Chul Hyoung; Liow, Jeih-San; Snow, Joseph; Page, Emily; Jenko, Kimberly J.; Morse, Cheryl L.; Zoghbi, Sami S.; Pike, Victor W.; Turner, R. Scott; Innis, Robert B. (Neurobiology of aging, 2017)
We sought to determine whether patients with posterior cortical atrophy (PCA) demonstrate a pattern of binding to translocator protein 18 kDa, a marker of microglial activation, that is distinct from that in patients with amnestic presentation of Alzheimer's disease (AD). Eleven PCA patients, 11 amnestic AD patients, and 15 age-matched controls underwent positron emission tomography with 11C-PBR28 to measure translocator protein 18 kDa. PCA patients showed greater 11C-PBR28 binding than controls in occipital, posterior parietal, and temporal regions. In contrast, amnestic AD patients showed greater 11C-PBR28 binding in inferior and medial temporal cortex. Increased 11C-PBR28 binding overlapped with reduced cortical volume for both PCA and amnestic AD patients, and with areas of reduced glucose metabolism in PCA patients. While both patient groups showed diffuse amyloid binding, PCA patients showed greater binding than amnestic AD patients in bilateral occipital cortex. These results suggest that microglial activation is closely associated with neurodegeneration across different subtypes of AD.